mirror of
https://github.com/MartinThoma/LaTeX-examples.git
synced 2025-04-26 06:48:04 +02:00
many improvements (theorem-proof-structure for constant function; corrected errors)
This commit is contained in:
parent
01e343f66c
commit
a1274e176f
10 changed files with 163 additions and 123 deletions
|
@ -64,9 +64,19 @@ This result means:
|
|||
\clearpage
|
||||
|
||||
\section{Defined on a closed interval $[a,b] \subseteq \mdr$}
|
||||
\begin{theorem}[Solution formula for constant functions]
|
||||
Let $f:[a,b] \rightarrow \mdr$, $f(x) := c$ with $a,b,c \in \mdr$ and
|
||||
$a \leq b$ be a constant function.
|
||||
|
||||
Then the point $(x, f(x))$ of $f$ with minimal distance to $P$ is
|
||||
given by:
|
||||
\[\underset{x\in [a,b]}{\arg \min d_{P,f}(x)} = \begin{cases}
|
||||
S_0(f,P) &\text{if } S_0(f,P) \cap [a,b] \neq \emptyset \\
|
||||
\Set{a} &\text{if } S_0(f,P) \ni x_P < a\\
|
||||
\Set{b} &\text{if } S_0(f,P) \ni x_P > b
|
||||
\end{cases}\]
|
||||
\end{theorem}
|
||||
|
||||
\begin{figure}[htp]
|
||||
\centering
|
||||
\begin{tikzpicture}
|
||||
|
@ -111,17 +121,16 @@ $a \leq b$ be a constant function.
|
|||
\label{fig:constant-min-distance-closed-intervall}
|
||||
\end{figure}
|
||||
|
||||
The point with minimum distance can be found by:
|
||||
\[\underset{x\in\mdr}{\arg \min d_{P,f}(x)} = \begin{cases}
|
||||
S_0(f,P) &\text{if } S_0(f,P) \cap [a,b] \neq \emptyset \\
|
||||
\Set{a} &\text{if } S_0(f,P) \ni x_P < a\\
|
||||
\Set{b} &\text{if } S_0(f,P) \ni x_P > b
|
||||
\end{cases}\]
|
||||
|
||||
Because:
|
||||
\begin{proof}
|
||||
\begin{align}
|
||||
\underset{x\in[a,b]}{\arg \min d_{P,f}(x)} &= \underset{x\in[a,b]}{\arg \min d_{P,f}(x)^2}\\
|
||||
&=\underset{x\in[a,b]}{\arg \min} x^2 - 2x_P x + (x_P^2 + y_P^2 - 2 y_P c + c^2)\\
|
||||
&=\underset{x\in[a,b]}{\arg \min} x^2 - 2 x_P x + x_P^2\\
|
||||
&=\underset{x\in[a,b]}{\arg \min} \big (x^2 - 2x_P x + x_P^2 + \overbrace{(y_P^2 - 2 y_P c + c^2)}^{\text{constant}} \big )\\
|
||||
&=\underset{x\in[a,b]}{\arg \min} (x^2 - 2 x_P x + x_P^2)\\
|
||||
&=\underset{x\in[a,b]}{\arg \min} (x-x_P)^2
|
||||
\end{align}
|
||||
|
||||
which is optimal for $x = x_P$, but if $x_P \notin [a,b]$, you want
|
||||
to make this term as small as possible. It gets as small as possible when
|
||||
$x$ is as similar to $x_p$ as possible. This yields directly to the
|
||||
solution formula.$\qed$
|
||||
\end{proof}
|
||||
|
|
|
@ -5,7 +5,9 @@ paths are cubic splines. You also have to be able to calculate
|
|||
how to steer to get or to remain on a path. A way to do this
|
||||
is applying the \href{https://en.wikipedia.org/wiki/PID_algorithm}{PID algorithm}.
|
||||
This algorithm needs to know the signed current error. So you need to
|
||||
be able to get the minimal distance of a point to a cubic spline combined with the direction (left or right).
|
||||
be able to get the minimal distance of a point (the position of the car)
|
||||
to a cubic spline (the prefered path)
|
||||
combined with the direction (left or right).
|
||||
As you need to get the signed error (and one steering direction might
|
||||
be prefered), it is not only necessary to
|
||||
get the minimal absolute distance, but might also help to get all points
|
||||
|
@ -22,3 +24,8 @@ of the underlying PID-related problem. So I will try to give
|
|||
robust and easy-to-implement algorithms to calculated the distance
|
||||
of a point to a (piecewise or global) defined polynomial function
|
||||
of degree $\leq 3$.
|
||||
|
||||
When you're able to calculate the distance to a polynomial which is
|
||||
defined on a closed invervall, you can calculate the distance from
|
||||
a point to a spline by calculating the distance to the pieces of the
|
||||
spline.
|
||||
|
|
|
@ -1,7 +1,13 @@
|
|||
\chapter{Linear function}
|
||||
\section{Defined on $\mdr$}
|
||||
Let $f(x) = m \cdot x + t$ with $m \in \mdr \setminus \Set{0}$ and
|
||||
$t \in \mdr$ be a linear function.
|
||||
\begin{theorem}[Solution formula for linear functions on $\mdr$]
|
||||
Let $f: \mdr \rightarrow \mdr $ be a linear function
|
||||
$f(x) := m \cdot x + t$ with $m \in \mdr \setminus \Set{0}$ and
|
||||
$t \in \mdr$ be a linear function.
|
||||
|
||||
Then the points $(x, f(x))$ with minimal distance are given by:
|
||||
\[x = \frac{m}{m^2+1} \left ( y_P + \frac{1}{m} \cdot x_P - t \right )\]
|
||||
\end{theorem}
|
||||
|
||||
\begin{figure}[htp]
|
||||
\centering
|
||||
|
@ -39,30 +45,32 @@ $t \in \mdr$ be a linear function.
|
|||
\label{fig:linear-min-distance}
|
||||
\end{figure}
|
||||
|
||||
Now you can drop a perpendicular $f_\bot$ through $P$ on $f(x)$. The
|
||||
slope of $f_\bot$ is $- \frac{1}{m}$ and $t_\bot$ can be calculated:\nobreak
|
||||
\begin{align}
|
||||
f_\bot(x) &= - \frac{1}{m} \cdot x + t_\bot\\
|
||||
\Rightarrow y_P &= - \frac{1}{m} \cdot x_P + t_\bot\\
|
||||
\Leftrightarrow t_\bot &= y_P + \frac{1}{m} \cdot x_P
|
||||
\end{align}
|
||||
\begin{proof}
|
||||
Now you can drop a perpendicular $f_\bot$ through $P$ on $f(x)$. The
|
||||
slope of $f_\bot$ is $- \frac{1}{m}$ and $t_\bot$ can be calculated:\nobreak
|
||||
\begin{align}
|
||||
f_\bot(x) &= - \frac{1}{m} \cdot x + t_\bot\\
|
||||
\Rightarrow y_P &= - \frac{1}{m} \cdot x_P + t_\bot\\
|
||||
\Leftrightarrow t_\bot &= y_P + \frac{1}{m} \cdot x_P
|
||||
\end{align}
|
||||
|
||||
The point $(x, f(x))$ where the perpendicular $f_\bot$ crosses $f$
|
||||
is calculated this way:
|
||||
\begin{align}
|
||||
f(x) &= f_\bot(x)\\
|
||||
\Leftrightarrow m \cdot x + t &= - \frac{1}{m} \cdot x + \left(y_P + \frac{1}{m} \cdot x_P \right)\\
|
||||
\Leftrightarrow \left (m + \frac{1}{m} \right ) \cdot x &= y_P + \frac{1}{m} \cdot x_P - t\\
|
||||
\Leftrightarrow x &= \frac{m}{m^2+1} \left ( y_P + \frac{1}{m} \cdot x_P - t \right )\label{eq:solution-of-the-linear-problem}
|
||||
\end{align}
|
||||
The point $(x, f(x))$ where the perpendicular $f_\bot$ crosses $f$
|
||||
is calculated this way:
|
||||
\begin{align}
|
||||
f(x) &= f_\bot(x)\\
|
||||
\Leftrightarrow m \cdot x + t &= - \frac{1}{m} \cdot x + \left(y_P + \frac{1}{m} \cdot x_P \right)\\
|
||||
\Leftrightarrow \left (m + \frac{1}{m} \right ) \cdot x &= y_P + \frac{1}{m} \cdot x_P - t\\
|
||||
\Leftrightarrow x &= \frac{m}{m^2+1} \left ( y_P + \frac{1}{m} \cdot x_P - t \right )\label{eq:solution-of-the-linear-problem}
|
||||
\end{align}
|
||||
|
||||
There is only one point with minimal distance. I'll call the result
|
||||
from line~\ref{eq:solution-of-the-linear-problem} \enquote{solution of
|
||||
the linear problem} and the function that gives this solution
|
||||
$S_1(f,P)$.
|
||||
There is only one point with minimal distance. I'll call the result
|
||||
from line~\ref{eq:solution-of-the-linear-problem} \enquote{solution of
|
||||
the linear problem} and the function that gives this solution
|
||||
$S_1(f,P)$.
|
||||
|
||||
See Figure~\ref{fig:linear-min-distance}
|
||||
to get intuition about the geometry used.
|
||||
See Figure~\ref{fig:linear-min-distance}
|
||||
to get intuition about the geometry used. $\qed$
|
||||
\end{proof}
|
||||
\clearpage
|
||||
|
||||
\section{Defined on a closed interval $[a,b] \subseteq \mdr$}
|
||||
|
|
Binary file not shown.
|
@ -40,13 +40,13 @@
|
|||
\newtheorem{proof}{Proof:}
|
||||
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
|
||||
|
||||
\title{Minimal distance to polynomial functions of degree 3 or less}
|
||||
\title{Minimal distance from a point to polynomial functions of degree 3 or less}
|
||||
\author{Martin Thoma}
|
||||
|
||||
\hypersetup{
|
||||
pdfauthor = {Martin Thoma},
|
||||
pdfkeywords = {minimal distance, polynomial, function, degree 3, cubic, spline},
|
||||
pdftitle = {Minimal distance to polynomial functions of degree 3 or less}
|
||||
pdftitle = {Minimal distance from a point to polynomial functions of degree 3 or less}
|
||||
}
|
||||
|
||||
\def\mdr{\ensuremath{\mathbb{R}}}
|
||||
|
|
|
@ -3,7 +3,7 @@ Let $f: D \rightarrow \mdr$ with $D \subseteq \mdr$ be a polynomial function and
|
|||
be a point. Let $d_{P,f}: \mdr \rightarrow \mdr_0^+$
|
||||
be the Euklidean distance of a point $P$ to a point $\left (x, f(x) \right )$
|
||||
on the graph of $f$:
|
||||
\[d_{P,f} (x) := \sqrt{(x_P - x)^2 + (y_P - f(x))^2}\]
|
||||
\[d_{P,f} (x) := \sqrt{(x - x_P)^2 + (f(x) - y_P)^2}\]
|
||||
|
||||
Now there is finite set $M = \Set{x_1, \dots, x_n} \subseteq D$ of minima for given $f$ and $P$:
|
||||
\[M = \Set{x \in D | d_{P,f}(x) = \min_{\overline{x} \in D} d_{P,f}(\overline{x})}\]
|
||||
|
@ -20,6 +20,11 @@ about stationary points will be tremendously usefull:
|
|||
Then: $f'(x_0) = 0$.
|
||||
\end{theorem}
|
||||
|
||||
So in fact you can calculate the roots of $(d_{P,f}(x))'$ to get
|
||||
candidates for minimal distance. These candidates include all points
|
||||
with minimal distance, but might also contain more. Example~\ref{ex:false-positive}
|
||||
shows such a situation.
|
||||
|
||||
Let $S_n$ be the function that returns the set of solutions for a
|
||||
polynomial $f$ of degree $n$ and a point $P$:
|
||||
|
||||
|
|
|
@ -0,0 +1,47 @@
|
|||
$4 \alpha^3 + 27 \beta^2 \geq 0$:
|
||||
The solution of Equation~\ref{eq:simple-cubic-equation-for-quadratic-distance}
|
||||
is
|
||||
\[x = \frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t}\]
|
||||
|
||||
When you insert this in Equation~\ref{eq:simple-cubic-equation-for-quadratic-distance}
|
||||
you get:\footnote{Remember: $(a-b)^3 = a^3-3 a^2 b+3 a b^2-b^3$}
|
||||
\allowdisplaybreaks
|
||||
\begin{align}
|
||||
0 &\stackrel{!}{=} \left (\frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \right )^3 + \alpha \left (\frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \right ) + \beta\\
|
||||
&= (\frac{t}{\sqrt[3]{18}})^3
|
||||
- 3 (\frac{t}{\sqrt[3]{18}})^2 \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t}
|
||||
+ 3 (\frac{t}{\sqrt[3]{18}})(\frac{\sqrt[3]{\frac{2}{3}} \alpha }{t})^2
|
||||
- (\frac{\sqrt[3]{\frac{2}{3}} \alpha }{t})^3
|
||||
+ \alpha \left (\frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \right ) + \beta\\
|
||||
&= \frac{t^3}{18}
|
||||
- \frac{3t^2}{\sqrt[3]{18^2}} \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t}
|
||||
+ \frac{3t}{\sqrt[3]{18}} \frac{\sqrt[3]{\frac{4}{9}} \alpha^2 }{t^2}
|
||||
- \frac{\frac{2}{3} \alpha^3 }{t^3}
|
||||
+ \alpha \left (\frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \right ) + \beta\\
|
||||
&= \frac{t^3}{18}
|
||||
- \frac{\sqrt[3]{18} t \alpha}{\sqrt[3]{18^2}}
|
||||
+ \frac{\sqrt[3]{12} \alpha^2}{\sqrt[3]{18} t}
|
||||
- \frac{2 \alpha^3 }{3t^3}
|
||||
+ \alpha \left (\frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \right ) + \beta\\
|
||||
&= \frac{t^3}{18}
|
||||
- \frac{t \alpha}{\sqrt[3]{18}}
|
||||
\color{red}+ \frac{\sqrt[3]{2} \alpha^2}{\sqrt[3]{3} t} \color{black}
|
||||
- \frac{2 \alpha^3 }{3 t^3}
|
||||
+ \color{red}\alpha \color{black} \left (\frac{t}{\sqrt[3]{18}} \color{red}- \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \color{black}\right )
|
||||
+ \beta\\
|
||||
&= \frac{t^3}{18} \color{blue}- \frac{t \alpha}{\sqrt[3]{18}} \color{black}
|
||||
- \frac{2 \alpha^3 }{3 t^3}
|
||||
\color{blue}+ \frac{\alpha t}{\sqrt[3]{18}} \color{black}
|
||||
+ \beta\\
|
||||
&= \frac{t^3}{18} - \frac{2 \alpha^3 }{3 t^3} + \beta\\
|
||||
&= \frac{t^6 - 12 \alpha^3 + \beta 18 t^3}{18t^3}
|
||||
\end{align}
|
||||
|
||||
Now only go on calculating with the numerator. Start with resubstituting
|
||||
$t$:
|
||||
\begin{align}
|
||||
0 &= (\sqrt{3 \cdot (4 \alpha^3 + 27 \beta^2)} -9\beta)^2 - 12 \alpha^3 + \beta 18 (\sqrt{3 \cdot (4 \alpha^3 + 27 \beta^2)} -9\beta)\\
|
||||
&= (\sqrt{3 \cdot (4 \alpha^3 + 27 \beta^2)})^2 +(9\beta)^2 - 12 \alpha^3 -(2 \cdot 9)\cdot 9\beta^2\\
|
||||
&= 3 \cdot (4 \alpha^3 + 27 \beta^2) -81 \beta^2 - 12 \alpha^3\\
|
||||
&= 0
|
||||
\end{align}
|
|
@ -1,8 +1,8 @@
|
|||
\todo[inline]{calculate...}
|
||||
|
||||
One solution is
|
||||
\[x = \frac{(1+i \sqrt{3})\alpha}{\sqrt[3]{12} \cdot t}
|
||||
-\frac{(1-i\sqrt{3}) t}{2\sqrt[3]{18}}\]
|
||||
|
||||
We will verify it in multiple steps. First, get $x^3$:
|
||||
\begin{align}
|
||||
x^3 &= \underbrace{\left (\frac{(1+i\sqrt{3})\alpha}{\sqrt[3]{12} \cdot t} \right)^3}_{=: \raisebox{.5pt}{\textcircled{\raisebox{-.9pt} {1}}}}
|
||||
\underbrace{- 3 \left(\frac{(1+i\sqrt{3})\alpha}{\sqrt[3]{12} \cdot t} \right)^2 \left(\frac{(1-i\sqrt{3})t}{2 \sqrt[3]{18}} \right)}_{=: \raisebox{.5pt}{\textcircled{\raisebox{-.9pt} {2}}}}\\
|
||||
|
@ -10,26 +10,23 @@
|
|||
\underbrace{- \left(\frac{(1-i\sqrt{3})t}{2 \sqrt[3]{18}}\right)^3}_{=: \raisebox{.5pt}{\textcircled{\raisebox{-.9pt} {4}}}}
|
||||
\end{align}
|
||||
|
||||
Now simplify the summands:
|
||||
Now simplify the summands of $x^3$:
|
||||
\begin{align}
|
||||
\raisebox{.5pt}{\textcircled{\raisebox{-.9pt} {1}}} &=
|
||||
\left (\frac{(1+i\sqrt{3})\alpha}{\sqrt[3]{12} \cdot t} \right)^3\\
|
||||
&= \frac{\alpha^3(1-3i\sqrt{3} - 3 \cdot 3 + \sqrt{27} i)}{12 t^3}\\
|
||||
&= \frac{-8\alpha^3}{12 t^3}\\
|
||||
&= \frac{-2 \alpha^3}{3 t^3}\\
|
||||
\raisebox{.5pt}{\textcircled{\raisebox{-.9pt} {2}}} &=- 3 \left(\frac{(1+i\sqrt{3})\alpha}{\sqrt[3]{12} \cdot t} \right)^2 \left(\frac{(1-i\sqrt{3})t}{2 \sqrt[3]{18}} \right)\\
|
||||
&= \frac{-3\alpha^2(1+2\sqrt{3}i-3)(1-i\sqrt{3})t}{t^2 \sqrt[3]{2^4 \cdot 3^2} \cdot 2 \sqrt[3]{2 \cdot 3^2}}\\
|
||||
&= \frac{-3\alpha^2((1+2\sqrt{3}i - 3)+(- i\sqrt{3}+2\cdot 3 + i\sqrt{3}))}{12 t \sqrt[3]{12}}\\
|
||||
&= \frac{-\alpha^2(4+2\sqrt{3}i)}{4t\sqrt[3]{12}}\\
|
||||
&= \frac{-\alpha^2(2+\sqrt{3}i)}{2t\sqrt[3]{12}}\\
|
||||
&= \frac{-3\alpha^2(-2(1-i\sqrt{3}))(1-i\sqrt{3})t}{t^2 \sqrt[3]{2^4 \cdot 3^2} \cdot 2 \sqrt[3]{2 \cdot 3^2}}\\
|
||||
&= \frac{6\alpha^2 t (-2 (1+i \sqrt{3}))}{12 t^2 \sqrt[3]{12}}\\
|
||||
&= \frac{- \alpha^2 (1+i\sqrt{3})}{t\sqrt[3]{12}}\\
|
||||
\raisebox{.5pt}{\textcircled{\raisebox{-.9pt} {3}}} &= 3 \left(\frac{(1+i\sqrt{3})\alpha}{\sqrt[3]{12} \cdot t} \right) \left(\frac{(1-i\sqrt{3})t}{2 \sqrt[3]{18}}\right)^2\\
|
||||
&= \frac{3(1+i\sqrt{3})\alpha (1-2i\sqrt{3} - 3)t}{4 \sqrt[3]{12 \cdot 18^2}}\\
|
||||
&= \frac{3 \alpha t((1-2i\sqrt{3}-3)+(i\sqrt{3} + 2\cdot 3 - 3i\sqrt{3}))}{4 \sqrt[3]{2^2 \cdot 3 \cdot (2 \cdot 3^2)^2}}\\
|
||||
&= \frac{3 \alpha t(4-4\sqrt{3}i)}{4 \cdot 2 \cdot 3 \sqrt[3]{2 \cdot 3^2}}\\
|
||||
&= \frac{\alpha t(1-\sqrt{3}i)}{2\sqrt[3]{18}}\\
|
||||
&= \frac{3\alpha t (1+i\sqrt{3})(-2(1+i\sqrt{3}))}{4 \cdot \sqrt[3]{12 \cdot 18^2}}\\
|
||||
&= \frac{-\alpha t (-2 (1 - i \sqrt{3}))}{2 \sqrt[3]{12 \cdot 4 \cdot 3}}\\
|
||||
&= \frac{\alpha t (1-i\sqrt{3})}{\sqrt[3]{2^4 \cdot 3^2}}\\
|
||||
&= \frac{\alpha t (1-i\sqrt{3}}{2 \sqrt[3]{18}}\\
|
||||
\raisebox{.5pt}{\textcircled{\raisebox{-.9pt} {4}}} &= - \left(\frac{(1-i\sqrt{3})t}{2 \sqrt[3]{18}}\right)^3\\
|
||||
&= -\frac{(1-3i\sqrt{3} - 3 \cdot 3 + i \sqrt{27}) t^3}{8 \cdot 18}\\
|
||||
&=- \frac{t^3 (-8)}{8 \cdot 18}\\
|
||||
&=- \frac{(-8) t^3}{8 \cdot 18}\\
|
||||
&= \frac{t^3}{18}
|
||||
\end{align}
|
||||
|
||||
|
@ -37,10 +34,10 @@ Now get back to the original equation:
|
|||
\begin{align}
|
||||
0 &\stackrel{!}{=} x^3 + \alpha x + \beta \\
|
||||
&= \left (\frac{-2 \alpha^3}{3 t^3}
|
||||
+ \frac{-\alpha^2(2+\sqrt{3}i)}{2t\sqrt[3]{12}}
|
||||
+ \color{red}\frac{-\alpha^2(1+\sqrt{3}i)}{t\sqrt[3]{12}}\color{black}
|
||||
+ \color{blue}\frac{\alpha t(1-\sqrt{3}i)}{2\sqrt[3]{18}}\color{black}
|
||||
+ \frac{t^3}{18} \right )\\
|
||||
&\hphantom{{}=} + \color{blue}\alpha\color{black} \left (\frac{(1+i \sqrt{3})\alpha}{\sqrt[3]{12} \cdot t}
|
||||
&\hphantom{{}=} + \alpha \left (\color{red}\frac{(1+i \sqrt{3})\alpha}{\sqrt[3]{12} \cdot t} \color{black}
|
||||
\color{blue}-\frac{(1-i\sqrt{3}) t}{2\sqrt[3]{18}} \color{black} \right ) + \beta\\
|
||||
&= \frac{-2 \alpha^3}{3 t^3}
|
||||
+ \frac{\alpha^2(2(1+i\sqrt{3})-(2+\sqrt{3}i))}{2t\sqrt[3]{12}}
|
||||
|
|
|
@ -10,8 +10,7 @@
|
|||
&= 12 \cdot \bigg (\frac{\overbrace{\sqrt[3]{12} \alpha (1-i \sqrt{3}) - t^2(1+i\sqrt{3})}^{\text{numerator}}}{12t} \bigg )^3
|
||||
\end{align}
|
||||
|
||||
Now calculate the numerator$^3$. Remember, that $(1-i \sqrt{3})^2 = -2 (1+i \sqrt{3})$
|
||||
and $(1 \pm i \sqrt{3})^3 = -8$.
|
||||
Now calculate the numerator$^3$:
|
||||
\begin{align}
|
||||
\left (\sqrt[3]{12} \alpha (1-i \sqrt{3}) - t^2(1+i\sqrt{3}) \right )^3 &=
|
||||
12 \alpha^3 (1-i\sqrt{3})^3 \\
|
||||
|
|
|
@ -59,18 +59,22 @@ There can be up to 3 solutions in such an equation. Those solutions
|
|||
can be found with a closed formula. But not every solution of the
|
||||
equation given by Theorem~\ref{thm:fermats-theorem}
|
||||
has to be a solution to the given problem.
|
||||
|
||||
\begin{example}
|
||||
\goodbreak
|
||||
\begin{example}\label{ex:false-positive}
|
||||
Let $a = 1, b = 0, c= 1, x_p= 0, y_p = 1$.
|
||||
So $f(x) = x^2 + 1$ and $P(0, 1)$.
|
||||
|
||||
\begin{align}
|
||||
0 &\stackrel{!}{=} 4 x^3 - 2x\\
|
||||
&=2x(2x^2 - 1)\\
|
||||
\Rightarrow x_1 &= 0 \;\;\; x_{2,3} = \pm \frac{1}{\sqrt{2}}
|
||||
\end{align}
|
||||
|
||||
As you can easily verify, only $x_1$ is a minimum of $d_{P,f}$.
|
||||
So $f(x) = x^2 - 1$ and $P(0, 1)$.
|
||||
\begin{align}
|
||||
\xRightarrow{\text{Equation}~\ref{eq:quadratic-derivative-eq-0}} 0 &\stackrel{!}{=} 2x^3 - 3x\\
|
||||
&= x(2x^2-3)\\
|
||||
\Rightarrow x_{1,2} &= \pm \sqrt{\frac{3}{2}} \text{ and } x_3 = 0\\
|
||||
d_{P,f}(x_3) &= \sqrt{0^2 + (-1-1)^2} = 2\\
|
||||
d_{P,f} \left (+ \sqrt{\frac{3}{2}} \right ) &= \sqrt{\left (\sqrt{\frac{3}{2} - 0} \right )^2 + \left (\frac{1}{2}-1 \right )^2}\\
|
||||
&= \sqrt{\nicefrac{3}{2}+\nicefrac{1}{4}} \\
|
||||
&= \sqrt{\nicefrac{7}{4}}\\
|
||||
&= d_{P,f} \left (- \sqrt{\frac{3}{2}} \right )
|
||||
\end{align}
|
||||
This means $x_3$ is not a point of minimal distance, but with
|
||||
$(d_{P,f}(x_3))' = 0$.
|
||||
\end{example}
|
||||
|
||||
|
||||
|
@ -81,8 +85,12 @@ As you can easily verify, only $x_1$ is a minimum of $d_{P,f}$.
|
|||
\end{theorem}
|
||||
|
||||
\begin{proof}
|
||||
The number of closests points of $f$ cannot be bigger than 3, because
|
||||
Equation~\ref{eq:quadratic-derivative-eq-0} is a polynomial function
|
||||
of degree 3. Such a function can have at most 3 roots.
|
||||
|
||||
In the following, I will do some transformations with $f = f_0$ and
|
||||
$P = P_0$ .
|
||||
$P = P_0$.
|
||||
|
||||
Moving $f_0$ and $P_0$ simultaneously in $x$ or $y$ direction does
|
||||
not change the minimum distance. Furthermore, we can find the
|
||||
|
@ -95,8 +103,8 @@ First of all, we move $f_0$ and $P_0$ by $\frac{b}{2a}$ in $x$ direction, so
|
|||
Because:\footnote{The idea why you subtract $\frac{b}{2a}$ within
|
||||
$f$ is that when you subtract something from $x$ before applying
|
||||
$f$ it takes more time ($x$ needs to be bigger) to get to the same
|
||||
situation. So to move the whole graph by $1$ to the left whe have
|
||||
to add $+1$.}
|
||||
situation. In consequence, if we want to move the whole graph by 1
|
||||
to the left, we have to add $+1$.}
|
||||
\begin{align}
|
||||
f(x-\nicefrac{b}{2a}) &= a (x-\nicefrac{b}{2a})^2 + b (x-\nicefrac{b}{2a}) + c\\
|
||||
&= a (x^2 - \nicefrac{b}{a} x + \nicefrac{b^2}{4a^2}) + bx - \nicefrac{b^2}{2a} + c\\
|
||||
|
@ -117,15 +125,15 @@ Then compute:
|
|||
&= \sqrt{x^2 + (ax^2-w)^2}\\
|
||||
&= \sqrt{x^2 + a^2 x^4-2aw x^2+w^2}\\
|
||||
&= \sqrt{a^2 x^4 + (1-2aw) x^2 + w^2}\\
|
||||
&= \sqrt{\left (a^2 x^2 + \frac{1-2 a w}{2} \right )^2 + w^2 - (1-2 a w)^2}\\
|
||||
&= \sqrt{\left (a^2 x^2 + \nicefrac{1}{2}-a w \right )^2 + \big (w^2 - (1-2 a w)^2 \big)}
|
||||
&= \sqrt{\left (a x^2 + \frac{1-2 a w}{2a} \right )^2 + w^2 - (\frac{1-2 a w}{2a})^2}\\
|
||||
&= \sqrt{\left (a x^2 + \nicefrac{1}{2a}- w \right )^2 + \big (w^2 - (\frac{1-2 a w}{2a})^2 \big)}
|
||||
\end{align}
|
||||
|
||||
The term
|
||||
\[a^2 x^2 + (\nicefrac{1}{2}-a w)\]
|
||||
\[a^2 x^2 + (\nicefrac{1}{2a}- w)\]
|
||||
should get as close to $0$ as possilbe when we want to minimize
|
||||
$d_{P,{f_2}}$. For $w \leq \nicefrac{1}{2a}$ you only have $x = 0$ as a minimum.
|
||||
For all other points $P = (0, w)$, there are exactly two minima $x_{1,2} = \pm \sqrt{aw - \nicefrac{1}{2}}$.
|
||||
For all other points $P = (0, w)$, there are exactly two minima $x_{1,2} = \pm \sqrt{\frac{\frac{1}{2a} - w}{a}}$.
|
||||
$\qed$
|
||||
\end{proof}
|
||||
|
||||
|
@ -136,7 +144,7 @@ We start with the graph that was moved so that $f_2 = ax^2$.
|
|||
|
||||
In this case, we have already found the solution. If $w = y_P + \frac{b^2}{4a} - c > \frac{1}{2a}$,
|
||||
then there are two solutions:
|
||||
\[x_{1,2} = \pm \sqrt{aw - \nicefrac{1}{2}}\]
|
||||
\[x_{1,2} = \pm \sqrt{\frac{\frac{1}{2a} - w}{a}}\]
|
||||
Otherwise, there is only one solution $x_1 = 0$.
|
||||
|
||||
\textbf{Case 2:} $P = (z, w)$ is not on the symmetry axis, so $z \neq 0$. Then you compute:
|
||||
|
@ -147,8 +155,7 @@ Otherwise, there is only one solution $x_1 = 0$.
|
|||
0 &\stackrel{!}{=} \Big(\big(d_{P, {f_2}}(x)\big)^2\Big)' \\
|
||||
&= 4a^2x^3 + 2(1- 2 aw)x +(- 2z)\\
|
||||
&= 2 \left (2a^2x^2 + (1- 2 aw) \right )x - 2z\\
|
||||
\Leftrightarrow 0 &\stackrel{!}{=} (2a^2x^2 + (1- 2 aw)) x - z\\
|
||||
&= 2 a^2 x^3 + (1- 2 aw) x - z\\
|
||||
\Leftrightarrow 0 &\stackrel{!}{=} 2a^2x^3 + (1- 2 aw) x - z\\
|
||||
\Leftrightarrow 0 &\stackrel{!}{=} x^3 + \underbrace{\frac{1- 2 aw}{2 a^2}}_{=: \alpha} x + \underbrace{\frac{-z}{2 a^2}}_{=: \beta}\\
|
||||
&= x^3 + \alpha x + \beta\label{eq:simple-cubic-equation-for-quadratic-distance}
|
||||
\end{align}
|
||||
|
@ -156,54 +163,15 @@ Otherwise, there is only one solution $x_1 = 0$.
|
|||
Let $t$ be defined as
|
||||
\[t := \sqrt[3]{\sqrt{3 \cdot (4 \alpha^3 + 27 \beta^2)} -9\beta}\]
|
||||
|
||||
\textbf{Case 2.1:} $4 \alpha^3 + 27 \beta^2 \geq 0$:
|
||||
The solution of Equation~\ref{eq:simple-cubic-equation-for-quadratic-distance}
|
||||
is
|
||||
\[x = \frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t}\]
|
||||
I will make use of the following identities:
|
||||
\begin{align*}
|
||||
(1-i \sqrt{3})^2 &= -2 (1+i \sqrt{3})\\
|
||||
(1+i \sqrt{3})^2 &= -2 (1-i \sqrt{3})\\
|
||||
(1 \pm i \sqrt{3})^3 &= -8
|
||||
\end{align*}
|
||||
|
||||
When you insert this in Equation~\ref{eq:simple-cubic-equation-for-quadratic-distance}
|
||||
you get:\footnote{Remember: $(a-b)^3 = a^3-3 a^2 b+3 a b^2-b^3$}
|
||||
\allowdisplaybreaks
|
||||
\begin{align}
|
||||
0 &\stackrel{!}{=} \left (\frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \right )^3 + \alpha \left (\frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \right ) + \beta\\
|
||||
&= (\frac{t}{\sqrt[3]{18}})^3
|
||||
- 3 (\frac{t}{\sqrt[3]{18}})^2 \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t}
|
||||
+ 3 (\frac{t}{\sqrt[3]{18}})(\frac{\sqrt[3]{\frac{2}{3}} \alpha }{t})^2
|
||||
- (\frac{\sqrt[3]{\frac{2}{3}} \alpha }{t})^3
|
||||
+ \alpha \left (\frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \right ) + \beta\\
|
||||
&= \frac{t^3}{18}
|
||||
- \frac{3t^2}{\sqrt[3]{18^2}} \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t}
|
||||
+ \frac{3t}{\sqrt[3]{18}} \frac{\sqrt[3]{\frac{4}{9}} \alpha^2 }{t^2}
|
||||
- \frac{\frac{2}{3} \alpha^3 }{t^3}
|
||||
+ \alpha \left (\frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \right ) + \beta\\
|
||||
&= \frac{t^3}{18}
|
||||
- \frac{\sqrt[3]{18} t \alpha}{\sqrt[3]{18^2}}
|
||||
+ \frac{\sqrt[3]{12} \alpha^2}{\sqrt[3]{18} t}
|
||||
- \frac{\frac{2}{3} \alpha^3 }{t^3}
|
||||
+ \alpha \left (\frac{t}{\sqrt[3]{18}} - \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \right ) + \beta\\
|
||||
&= \frac{t^3}{18}
|
||||
- \frac{t \alpha}{\sqrt[3]{18}}
|
||||
\color{red}+ \frac{\sqrt[3]{2} \alpha^2}{\sqrt[3]{3} t} \color{black}
|
||||
- \frac{\frac{2}{3} \alpha^3 }{t^3}
|
||||
+ \color{red}\alpha \color{black} \left (\frac{t}{\sqrt[3]{18}} \color{red}- \frac{\sqrt[3]{\frac{2}{3}} \alpha }{t} \color{black}\right )
|
||||
+ \beta\\
|
||||
&= \frac{t^3}{18} \color{blue}- \frac{t \alpha}{\sqrt[3]{18}} \color{black}
|
||||
- \frac{\frac{2}{3} \alpha^3 }{t^3}
|
||||
\color{blue}+ \frac{\alpha t}{\sqrt[3]{18}} \color{black}
|
||||
+ \beta\\
|
||||
&= \frac{t^3}{18} - \frac{\frac{2}{3} \alpha^3 }{t^3} + \beta\\
|
||||
&= \frac{t^6 - 12 \alpha^3 + \beta 18 t^3}{18t^3}
|
||||
\end{align}
|
||||
|
||||
Now only go on calculating with the numerator. Start with resubstituting
|
||||
$t$:
|
||||
\begin{align}
|
||||
0 &= (\sqrt{3 \cdot (4 \alpha^3 + 27 \beta^2)} -9\beta)^2 - 12 \alpha^3 + \beta 18 (\sqrt{3 \cdot (4 \alpha^3 + 27 \beta^2)} -9\beta)\\
|
||||
&= (\sqrt{3 \cdot (4 \alpha^3 + 27 \beta^2)})^2 +(9\beta)^2 - 12 \alpha^3 -18\cdot 9\beta^2\\
|
||||
&= 3 \cdot (4 \alpha^3 + 27 \beta^2) -81 \beta^2 - 12 \alpha^3\\
|
||||
&= (4 \alpha^3 + 27 \beta^2) -27 \beta^2 - 4 \alpha^3\\
|
||||
&= 0
|
||||
\end{align}
|
||||
\textbf{Case 2.1:}
|
||||
\input{quadratic-case-2.1}
|
||||
|
||||
\textbf{Case 2.2:}
|
||||
\input{quadratic-case-2.2}
|
||||
|
|
Loading…
Add table
Add a link
Reference in a new issue